The effect of pH on the fat and protein within cream cheese and their influence on textural and rheological properties. (1st December 2020) - Ong, Lydia; Pax, Anita P.; Ong, Adabelle; Vongsvivut, Jitraporn; Tobin, Mark J.; Kentish, Sandra E.; Gras, Sally L.
Highlights: Variation in acid gel pH affects the microstructure of cream cheese. Greater protein hydration at pH 5.0 leads to bigger protein-fat aggregates. Reduced interaction between whey protein and casein contributes to softer cheese. Aggregated β-sheet protein increases and β-turn protein decreases in cheese at pH 4.3. Abstract: The effect of variation in acid gel pH during cream cheese production was investigated. The gel microstructure was denser and cheese texture firmer, as the pH decreased from pH 5.0 to pH 4.3, despite the viscoelasticity of these gels remaining similar during heating. Protein hydration and secondary structure appeared to be key factors affecting both cheese microstructure and properties. Proteins within the matrix appeared to swell at pH 5.0, leading to a larger corpuscular structure; greater β-turn structure was also observed by synchrotron-Fourier transform infrared (S-FTIR) microspectroscopy and the cheese was softer. A decrease in pH led to a denser microstructure with increased aggregated β-sheet structure and a firmer cheese. The higher whey protein loss at low pH likely contributed to increased cheese hardness. In summary, controlling the pH of acid gel is important, as this parameter affects proteins in the cheese, their secondary structure and the resulting cream cheese.